Germans against Nazism : nonconformity, opposition and resistance in the Third Reich : essays in Honour of Peter Hoffmann - Hoffmann, Peter, 1930-; Nicosia, Francis R., 1944-; Stokes, Lawrence D. (Berghahn Books, 2015)
Rather than being accepted by all of German society, the Nazi regime was resisted in both passive and active forms. This re-issued volume examines opposition to National Socialism by Germans during the Third Reich in its broadest sense. It considers individual and organized nonconformity, opposition, and resistance ranging from symbolic acts of disobedience to organized assassination attempts, and looks at how disparate groups such as the Jewish community, churches, conservatives, communists, socialists, and the military all defied the regime in their own ways.